An Empirical Study on the Integration of Programming and Mathematics Course in Primary Schools - Zhang, Jing; Han, Dong; Wang, Zhimin; Liu, Hongchao; Ma, Hongliang (2022 4th International Conference on Computer Science and Technologies in Education (CSTE), 2022)
With the rapid development of information technology and artificial intelligence, algorithm thinking has been regarded as one of the necessary skills for students. Meanwhile, the integration of programming and mathematics course has become an emerging research topic in interdisciplinary subject. Based on 5Es instructional framework, this study designed an interdisciplinary course which integrated block-based programming and mathematics, and conducted a quasi-experimental study among 105 fourth-grade students in a primary school. Quantitative data were collected through a mathematical attitude scale and knowledge test, as well as a rubric for students' programming artifacts. Qualitative data were collected by focus group interviews. The results showed that the interdisciplinary course had a positive impact on students' attitude towards mathematics, mathematics academic performance, and algorithmic thinking.